STUDENT LEARNING ACTIVITY RELATED TO CLASSROOM MANAGEMENT: HOW TEACHER ROLE? - Fidrayani; Sakinah Mawadah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to determine the significant positive relationship between classroom management and the learning activities of fourth grade students at MI El-Syifa Ciganjur. This type of research is descriptive correlational ex post facto (measurements before the incident). The population in this study was all students of class IV MI El-Syifa Ciganjur as many as 100 students with the research sample using a saturated sample. The data collection technique in this study used a Likert scale questionnaire on classroom management and student learning activities. The data analysis technique used is the product moment correlation technique, to determine the relationship and the coefficient of determination and to determine the contribution of class management variables to students' learning activity variables. The results of the research that have been obtained indicate that there is a significant positive relationship between classroom management and the learning activities of fourth grade students at MI El-Syifa Ciganjur with a correlation value (rxy) of 0.609 with the level of the relationship in the strong category. The result of the coefficient of determination in this study is 0.37, which means the contribution of the class management variable is 37% to the active learning of students.